Understanding Antimicrobial Resistance: From Mechanisms to Public Health Implications - Adhikary, Krishnendu; Ganguly, Krishnendu; Chakrabarty, Susmita; Sarkar, Riya; Nag, Riya; Srivastava, Sanchita; Barman, Saurav; Banerjee, Pradipta; Karak, Prithviraj; Ashique, Sumel; Hussain, Md Sadique (Current Pharmaceutical Biotechnology, 2025)
Antimicrobial resistance (AMR) is a global public health crisis driven by the overuse and misuse of antibiotics, inadequate infection control practices, and the evolution of microbes. It compromises the effective treatment of infections, posing severe implications for morbidity, mortality, and healthcare costs. Pathogens such as extended-spectrum β-lactamase (ESBL)-producing Escherichia coli and methicillin-resistant Staphylococcus aureus (MRSA) exemplify the growing threat of drug-resistant organisms. This review provides an in-depth analysis of the mechanisms underlying AMR, including enzymatic drug inactivation, efflux pump overexpression, target site modification, and biofilm formation. Additionally, it examines the clinical and economic implications of AMR and assesses emerging strategies for mitigation. Innovative solutions, such as bacteriophage therapy, CRISPR-based genome editing, and the One Health approach, offer promising avenues to address resistance across the human, animal, and environmental health sectors. Coordinated global efforts in surveillance, stewardship, and research are essential to curbing the spread and impact of AMR.
Keywords: one health